1 Del. Rev. Stat 410 (1893) - (:unkn) unknown (My University, 1893)
For the Protection Of Fish, Oysters, and Game, chap. 422, § 16: Prohibited trespassing on lands with a gun and/or a dog for the purpose of shooting birds or game. Violators shall pay a fine of five dollars and shall forfeit the gun until the fine is paid.
Keywords: HUNTING REGULATION